Organizational culture lecturer school high society - Рибалко, Л. С. (Scientific notes of the pedagogical department, 2017)
In this article installed, something neotъemlemoy sostavlyayuschey professionalism and teaching mastery javljaetsja lecturer jrganizational culture, development kotoroj make new oryentyrы high society in the pedagogical process of school. Otmecheno, something sformyrovannыe umenyya planyrovat, orhanyzovыvat, kontrolyrovat, korrektyrovat pedagogical process obespechyvayut development orhanyzatsyonnoy culture teachers. The concept specifies «organizational culture lecturer» as ability lecturer planyrovat orhanyzovыvat and pedagogical process, to build an mezhlychnostnыe collective relations in the principles of humanism and democracy.